Bowel and Bladder Care in Patients With Spinal Cord Injury. Issue 6 (15th March 2022) - Kuris, Eren O.; Alsoof, Daniel; Osorio, Camilo; Daniels, Alan H.
Abstract : Complete and incomplete spinal cord injuries affect between 250, 000 and 500, 000 people on an annual basis worldwide. In addition to sensory and motor dysfunction, spinal cord injury patients also suffer from associated conditions such as neurogenic bowel and bladder dysfunction. The degree of dysfunction varies on the level, degree, and type of spinal cord injury that occurs. In addition to the acute surgical treatment of these patients, spine surgeons should understand how to manage neurogenic bowel and bladder care on both a short- and long-term basis to minimize the risk for complications and optimize potential for rehabilitation.